Pengelolaan Perpustakaan Sekolah Terautomasi Berbasis SLiMS 9(Bulian) Di SMPN 4 Lubuk Alung Kabupaten Padang Pariaman - Desriyeni, Desriyeni; Ardoni, Ardoni; Habiburrahman, Habiburrahman (Ilmu Informasi Perpustakaan dan Kearsipan, 2021)
The purpose of this Community Partnership Program (PKM) activity is to solve school library problems in the application of information technology by providing understanding and skills in information technology-based school library management using the Senayan Library Management System (SLiMS) 9 Bulian application in accordance with the standards set for librarians or teachers. placed in the school library. In this activity, problems will be completely solved starting from understanding concepts and carrying out school library management practices by implementing a library automation system using the SLiMS 9 application. Judging from the priority problems set, the target output of the activity is that the librarian of SMPN 4 Lubuk Alung, Padang Pariaman is able to : (1) understand the meaning, nature, and function of information technology-based school libraries. At the end of the activity, a minimum of 75% of the PKM activity material can be mastered; (2) apply the knowledge gained in the management of an automated school library; and (3) the output target in the form of a process is that the SLiMS 9 application has been installed and used as a tool to replace various routine work in the library and library managers know and take advantage of various SLiMS 9 features that have been learned during the training, such as: data entry, label creation, barcoding, circulation services, membership, reporting, browsing, heading and subjecting. There is an increase in the ability of the target audience in understanding the understanding, concepts, and processes of managing and utilizing information technology-based school libraries.